Evaluasi biaya dan ekonomi dalam layanan kesehatan: A literature review - Sidarsyah Sidarsyah; Sartini Risky; Ilda Reski Ismail; La Ode Liaumin Azim (Holistik Jurnal Kesehatan, 2026)
Background: Healthcare services face significant challenges, including resource constraints, rising service costs, and unequal access driven by socio-economic disparities. These issues necessitate an approach capable of comprehensively assessing the efficiency and effectiveness of health interventions. Purpose: To analyze economic evaluation in healthcare services. Method: A Systematic Literature Review (SLR) approach adhering to PRISMA guidelines was employed. Literature searches were conducted across reputable scientific databases; inclusion criteria covered original articles published within the last decade that utilized economic evaluation methods such as cost-effectiveness analysis (CEA), cost-utility analysis (CUA), cost-benefit analysis (CBA), and cost-minimization analysis (CMA). Thirty articles met the criteria and were analyzed using narrative synthesis. Results: CEA and CUA are the most widely used methods, as they effectively illustrate the relationship between costs and health outcomes in a practical manner. Technology-based and preventive interventions tend to be more cost-effective in the long run, although outcomes are heavily influenced by the implementation context, population characteristics, and the specific analytical methods employed. Furthermore, findings vary across studies, and there are limitations regarding the integration of equity considerations into economic evaluations. Conclusion: Economic evaluation in healthcare plays a crucial role in assessing the efficiency and effectiveness of various medical interventions, with CEA and CUA serving as the dominant methods for measuring the relationship between costs and health outcomes. Suggestion: Future research should aim to develop more comprehensive economic evaluation approaches by integrating aspects of efficiency, equity, and sustainability. Additionally, employing standardized yet context-sensitive methodologies would enhance the relevance of findings in supporting evidence-based health policy formulation.   Keywords: Cost; Economics; Evaluation; Healthcare Services.